Successful induction of estrus during lactation for sows separated from their litters - Stevenson, Jeffrey S.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Our objective was to determine the effectiveness of inducing estrus during lactation by temporarily separating the litter from the sow during the last week of lactation. Lactating sows were removed daily from their litters for either 1) 3 hr /day (n=20), 2) 6 hr /day (n=39), or 3) 12 hr /day (n=10) during the last 8 days of lactation and exposed to an intact boar for at least 1 hr during the separation period. Litters were weaned from control sows at either 2 (n=13) or 4 (n=15) weeks for comparison of intervals to estrus following complete weaning or temporary separation. Estrus was observed in 13 of 20 (3 hr), 28 of 39 (6 hr) and 5 of 10 (12 hr) sows during 4 to 8 days after temporary separation periods began. Estrus was observed in 13 of 13 (2-wk weaning) and 13 of 16 (4-wk weaning) control sows from 2 to 8 days after weaning. Average intervals to estrus following temporary separation and weaning were similar (separation = 5.1 days and weaning = 4.6 days). Daily separation of sows for 3, 6, or 12 hr/day resulted in 45% (9/20) of the primiparous sows and 76% (37/49) of the multiparous sows showing synchronous estrus in 4 to 8 days after separation began.
Keywords: Swine; Estrus; Lactation; Litters